2011
DOI: 10.1161/hypertensionaha.110.165456
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverage, Sugar Intake of Individuals, and Their Blood Pressure

Abstract: Abstract-The obesity epidemic has focused attention on relationships of sugars and sugar-sweetened beverages (SSBs) to cardiovascular risk factors. Here we report cross-sectional associations of SSBs, diet beverages, and sugars with blood pressure (BP) for United Kingdom and US participants of the International Study of Macro/Micronutrients and Blood Pressure. Data collected include four 24-hour dietary recalls, two 24-hour urine collections, 8 BP readings, and questionnaire data for 2696 people ages 40 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
131
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(142 citation statements)
references
References 48 publications
7
131
0
4
Order By: Relevance
“…4,5 More recently, there are data to suggest that dietary factors, such as high consumption of carbohydrates, including sugars and soft drinks, could adversely influence BP levels. 6 A recent meta-analysis of intervention studies involving adults 7 shows that diets rich in carbohydrates may be associated with slightly higher BP. In contrast, dietary fiber intake was shown to be inversely associated with BP in adults 8 and with reduced risk of incident cardiovascular disease.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 More recently, there are data to suggest that dietary factors, such as high consumption of carbohydrates, including sugars and soft drinks, could adversely influence BP levels. 6 A recent meta-analysis of intervention studies involving adults 7 shows that diets rich in carbohydrates may be associated with slightly higher BP. In contrast, dietary fiber intake was shown to be inversely associated with BP in adults 8 and with reduced risk of incident cardiovascular disease.…”
mentioning
confidence: 99%
“…6,10 In addition, the National Health and Nutrition Examination Survey found that, in a sample of 4867 adolescents aged 12 to 18 years, higher sugar-sweetened beverage consumption was associated with higher serum uric acid levels and systolic BP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A likely mechanism may be that rapid uptake of sugar results in glycemic spikes which, if occurring frequently, may decrease vascular function by inducing oxidative stress, inflammation, and endothelial dysfunction (Node & Inoue, 2009). In other circumstances, intake of soft drinks with sugar has also been negatively associated with vascular function in terms of elevated blood pressure and increased risks of coronary heart disease (Brown et al, 2011, Huang, Huang, Tian, Yang, & Gu, 2014), preeclampsia (Borgen et al, 2012; Clausen et al, 2001), and preterm delivery in some (Englund‐Ogge et al, 2012, Petherick, Goran, & Wright, 2014), but not in another study (Halldorsson, Strom, Petersen, & Olsen, 2010). Women who exercise little or smoke may be more vulnerable to such effects (Di Francescomarino, Sciartilli, Di Valerio, Di Baldassarre, & Gallina, 2009, Gordon, Lavoie, Arsenault, Ditto, & Bacon, 2008).…”
Section: Discussionmentioning
confidence: 99%